CCD Optical Tomography System to Detect Solid Contamination in Crystal-Clear Water - Jamaludin J.; Rahim, RA; Rahiman, MHF; Rohani, JM (IEEE-Inst Electrical Electronics Engineers Inc, 2024)
Indexed by WOS/ Scopus